2020
DOI: 10.1016/j.bbi.2019.11.017
|View full text |Cite|
|
Sign up to set email alerts
|

Oligodendrocytes modulate the immune-inflammatory response in EAE via TNFR2 signaling

Abstract: The pleotropic cytokine tumor necrosis factor (TNF) is involved in the pathophysiology of multiple sclerosis (MS). In various models of MS, including experimental autoimmune encephalomyelitis (EAE), the membrane-bound form of TNF (tmTNF), which signals primarily via TNFR2, mediates protective and reparative effects, whereas the soluble form (solTNF), which signals primarily via TNFR1, promotes pro-inflammatory and detrimental functions. In this study, we investigated the role of TNFR2 expressed in the oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 63 publications
2
54
0
2
Order By: Relevance
“…Interestingly, recent work using the same animals showed that oligodendrocyte-TNFR2 not only promotes myelination, but also modulates the immune-inflammatory response in the early phase of EAE pathogenesis. In particular, specific ablation of oligodendroglial-TNFR2 resulted in increased microglia activation and blood brain barrier permeability, and accelerated infiltration of immune cells into the spinal cord prior to development of motor symptoms (Madsen et al, 2019). Further, opposing functions of microglial and macrophagic TNFR2 in the pathogenesis of EAE were reported.…”
Section: Degenerative Diseasesmentioning
confidence: 99%
“…Interestingly, recent work using the same animals showed that oligodendrocyte-TNFR2 not only promotes myelination, but also modulates the immune-inflammatory response in the early phase of EAE pathogenesis. In particular, specific ablation of oligodendroglial-TNFR2 resulted in increased microglia activation and blood brain barrier permeability, and accelerated infiltration of immune cells into the spinal cord prior to development of motor symptoms (Madsen et al, 2019). Further, opposing functions of microglial and macrophagic TNFR2 in the pathogenesis of EAE were reported.…”
Section: Degenerative Diseasesmentioning
confidence: 99%
“…Table 1 details all identified mouse models in which TNFR1 and TNFR2 were assessed independently. In brief, neurologic models have demonstrated even more complex effects of selective TNFR deletion; in EAE, TNFR2 is protective on microglia but deleterious on monocytes and macrophages whereas TNFR1 appears harmful in all contexts due to reducing the blood brain barrier function against cell infiltration into the CNS ( 84 , 105 , 117 ). In mouse models of pain, deletion of TNFR1 lead to reduction of mechanical pain as well as NMDA activation of lamina II neurons ( 86 , 87 , 134 ).…”
Section: Differential Tnfr Activity In Mouse Modelsmentioning
confidence: 99%
“…Importantly, treatment of the EAE mutant mice with the solTNF inhibitor XPro1595 was ineffective in the recovery of the symptoms, indicating that tmTNF can exert its beneficial effects of oligodendrocytes only in the presence of TNFR2 [ 98 ]. Moreover, lack of TNFR2 in oligodendrocytes induces an early activation of microglia, an increased BBB permeability and infiltration of immune cells in the spinal cord, leading to an accelerated onset and a higher disability peak, and to an overall increased severity of EAE [ 125 ]. This suggests that TNFR2 signaling in oligodendrocytes exert an immune-inflammatory function in EAE.…”
Section: Evidence For Tnf Involvement In Pathological Hallmarks Ofmentioning
confidence: 99%